The Influence of Management Accounting on Local Government Performance and the Implementation of the Nawacita Program: A Semantic Literature Review - Denny Kurnia (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This article explores the influence of management accounting practices on local government performance in Indonesia, focusing on the implementation of the Nawacita program, a national development agenda launched by President Joko Widodo. Through a comprehensive literature review using semantic analysis, the study examines how performance-based budgeting systems, particularly the Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP), interact with government management accounting tools to improve governance, fiscal transparency, and public accountability. The review synthesizes insights from various scholarly sources, identifying key themes such as institutional capacity, financial accountability, and strategic alignment with national development goals. The study highlights the pivotal role of management accounting systems in modernizing public financial management and ensuring that local governments’ budgeting processes are outcome-oriented rather than input-driven. Additionally, the review identifies several institutional challenges that hinder the effective implementation of PBB and SAKIP, such as weak governance structures, inadequate technical expertise, and resistance to change within local bureaucracies. Despite these challenges, the article underscores the opportunities for enhancing governance through improved capacity building, data systems, and alignment between local and national priorities. By addressing these challenges, the study concludes that local governments can better contribute to the success of the Nawacita program, achieving its goals of reducing inequality, improving public services, and fostering inclusive development. Ultimately, the article emphasizes the importance of institutional support and sustained commitment to reform for the successful integration of performance-based management tools in Indonesian local governance.